Sterculic Oil, a Natural SCD1 Inhibitor, Improves Glucose Tolerance in Obese ob/ob Mice. (14th November 2012) - Ortinau, Laura C.; Pickering, R. Taylor; Nickelson, Karen J.; Stromsdorfer, Kelly L.; Naik, Chaitasi Y.; Haynes, Rebecca A.; Bauman, Dale E.; Rector, R. Scott; Fritsche, Kevin L.; Perfield, James W.
Abstract : Obesity and its metabolic complications are associated with increased expression/activity of stearoyl-CoA desaturase-1 (SCD1), a major regulator of lipid metabolism. Reduction or ablation of this enzyme is associated with an improved metabolic profile and has gained attention as a target for pharmaceutical development. Sterculic oil (SO) is a known inhibitor of SCD1 and may provide a natural approach for treating obesity and/or insulin resistance. The purpose of this study was to evaluate the effects of SO consumption in leptin-deficient ob/ob mice, a model of obesity and insulin resistance. Five-week-old male mice received either an AIN-93G (control) or an AIN-93G diet containing 0.5% SO. After 9 weeks, SO supplementation did not alter food intake or body weight; however, the desaturase indices, a proxy of SCD1 activity, were reduced in liver and adipose tissue of SO-supplemented animals. This reduction was associated with improved glucose and insulin tolerance and attenuated hepatic inflammation in obese ob/ob mice, while no appreciable changes were observed in lean control mice receiving SO. Future studies are needed to better understand the mechanism(s) by which SO is functioning to improve glucose metabolism and to further explore the nutraceutical potential and health implications of SO supplementation.